Energy management of a dual‐mode power‐split powertrain based on the Pontryagin's minimum principle. Issue 9 (28th September 2017) - Ahmadizadeh, Pouyan; Mashadi, Behrooz; Lodaya, Dhaval
Abstract : A new dual‐mode power‐split device is introduced in this study for application in the transmission system of hybrid electric vehicles. The new system provides two modes of operation and a supervisory control strategy is responsible to determine the vehicle's present operating mode. Based on the selected mode, which is done according to the driving conditions, maximum efficiency and minimum fuel consumption are achieved. Pontryagin's minimum principle has been applied for designing an optimal control strategy during which the Hamiltonian is minimised. The Hamiltonian is calculated by using Pareto maps which provide best operating points of the engine according to the power demand. The simulation results show improvements in fuel consumption for the new system in comparison to the Toyota Hybrid System as the first commercialised and the most accepted and popular power‐split powertrain system.